Finite Element Analysis Predicts Large Optic Nerve Head Strains During Horizontal Eye Movements - Wang, Xiaofei; Rumpel, Helmut; Lim, Winston Eng Hoe; Baskaran, Mani; Perera, Shamira A.; Nongpiur, Monisha E.; Aung, Tin; Milea, Dan; Girard, Michaël J. A. (Investigative ophthalmology & visual science, 2016)
We combined finite element (FE) analysis and dynamic magnetic resonance imaging (MRI) to estimate optic nerve head (ONH) strains during horizontal eye movements, and identified factors influencing such strains. We also compared ONH strains (prelamina, lamina cribrosa, and retrolamina strains) induced by eye movements to those induced by IOP. The ocular globes and orbits of a healthy subject were visualized during horizontal eye movements (up to 13°), using dynamic MRI. A baseline FE model of one eye was reconstructed in the primary gaze position, including details from the orbital and ONH tissues. Finite element-derived ONH strains induced by eye movements were compared to those resulting from an IOP of 50 mm Hg. Finally, a FE sensitivity study was performed, in which we varied the stiffness of all ONH connective tissues, to understand their influence on ONH strains. Our models predicted that, during horizontal eye movements, the optic nerve pulled the ONH posteriorly. Optic nerve head strains following a lateral eye movement of 13° were large and higher than those resulting from an IOP of 50 mm Hg. These results held true even with variations in connective tissue stiffness. We also found that stiff sclerae reduced lamina cribrosa and prelamina strains during eye movements, but stiff optic nerve sheaths significantly increased those strains. Our models predicted high ONH strains during eye movements, which were aggravated with stiffer optic nerve sheaths. Further studies are needed to explore links between ONH strains induced by eye movements and axonal loss in glaucoma.